2021
DOI: 10.1039/d1ob01618k
|View full text |Cite
|
Sign up to set email alerts
|

An expeditious and highly efficient synthesis of substituted pyrroles using a low melting deep eutectic mixture

Abstract: An expeditious green method for the synthesis of diverse valued substituted pyrroles through a Paal–Knorr condensation reaction using a variety of amines and 2,5-hexanedione/2,5-dimethoxytetrahydrofuran in the presence of a low...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

6
2

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 87 publications
0
15
0
Order By: Relevance
“…Among the diverse green and sustainable surrogates, deep eutectic solvents (DESs), for the first time realized by Abbott’s group in 2003, have been continuously drawing a lot of attention of researchers globally, which can be inspected by a flow of scientific papers appearing in the literature day by day . The DESs in addition to exhibiting dual/triple features (solvent, catalyst, and/or reactant) in a reaction medium under consideration also display remarkable signatures including biodegradability, biocompatibility, atom economy, nonflammability, thermal stability, renewability, inexpensiveness, ease of handling, etc . Taking the above-said and other, if any, amazing features of DESs into consideration and with our current research interest toward the development of green protocols for simple and interesting molecules using DESs, herein, for the first time, we report a DES-mediated one-pot green synthesis of naphthalimide-centered acridine-1,8-dione derivatives through a multicomponent reaction of dimedone/cyclohexan-1,3-dione, hydrazine hydrate, 1,8-naphthanoic anhydride, and aromatic aldehydes. We believe that this useful eco-friendly methodology will open up new prospects for the construction of novel heterocyclic compounds in general and various interesting naphthalimide- and acridine-based conjugate molecular systems in particular.…”
Section: Introductionmentioning
confidence: 99%
“…Among the diverse green and sustainable surrogates, deep eutectic solvents (DESs), for the first time realized by Abbott’s group in 2003, have been continuously drawing a lot of attention of researchers globally, which can be inspected by a flow of scientific papers appearing in the literature day by day . The DESs in addition to exhibiting dual/triple features (solvent, catalyst, and/or reactant) in a reaction medium under consideration also display remarkable signatures including biodegradability, biocompatibility, atom economy, nonflammability, thermal stability, renewability, inexpensiveness, ease of handling, etc . Taking the above-said and other, if any, amazing features of DESs into consideration and with our current research interest toward the development of green protocols for simple and interesting molecules using DESs, herein, for the first time, we report a DES-mediated one-pot green synthesis of naphthalimide-centered acridine-1,8-dione derivatives through a multicomponent reaction of dimedone/cyclohexan-1,3-dione, hydrazine hydrate, 1,8-naphthanoic anhydride, and aromatic aldehydes. We believe that this useful eco-friendly methodology will open up new prospects for the construction of novel heterocyclic compounds in general and various interesting naphthalimide- and acridine-based conjugate molecular systems in particular.…”
Section: Introductionmentioning
confidence: 99%
“…Keeping the remarkable properties of DESs in mind, and also as our major research program in the construction of simple yet architecturally interesting molecules employing green protocols, we envisioned involving DES of choline chloride (ChCl) and l -(+)-tartaric acid (TA) for the Pechmann condensation reaction to generate a variety of substituted coumarin derivatives by reacting several substituted phenols with different β-ketoesters under operationally simple reaction conditions. To the best of our knowledge, this is the first report where DESs have been taken into the consideration toward the successful synthesis of coumarins.…”
Section: Introductionmentioning
confidence: 99%
“…1). [30][31][32][33][34][35] Considering the importance of these systems in a wide range of research fields and our major research programme to develop green synthetic protocols for various organic and supramolecular functional systems, [36][37][38][39][40][41][42][43] recently, our group also reported a simple and green approach for the preparation of diverse C4Ps in the presence of deep eutectic solvents (DES) of N,N′-dimethyl urea and L-(+)-tartaric acid. 44 Furthermore, recently, Wang and co-workers assembled various simple and functionalized C4P structures utilizing the chalcogen bonding (Se⋯O)-catalytic approach.…”
Section: Introductionmentioning
confidence: 99%
“…5). 84 Single-crystal X-ray studies revealed the partial cone conformation of the receptors (38)(39)(40) encapsulating a guest entity (45) in the form of 2 : 1 host-guest complexes (Fig. 5).…”
mentioning
confidence: 99%
See 1 more Smart Citation